Health and wellbeing status of the long-lived individuals of the Spanish LONGECYL cross-sectional study - Tomás Vega-Alonso; José Lozano-Alonso; Lorena Estévez-Iglesias; Ana Ordax-Díez; Enrique Arrieta-Antón; Ángel Díaz-Rodríguez; José-Luis Yañez-Ortega; Alejandro Santos-Lozano; Rocío Nuñez-Torres; María Perez-Caro; Gillermo Pita; Rosa Pinto-Labajo; et al. (Archives of Public Health, 2024)
Abstract Background The increase in life expectancy and long-lived individuals is a challenge for public health and provides an opportunity to understand the determinants of longevity. However, few studies have addressed the factors associated with the health status and quality of life in a long-lived individual population. We described the perceived health, clinical status, quality of life, and dependency for activities of daily living in a representative population in Castile and Leon, Spain. Methods A sample of 759 long-lived individuals aged 95 years and older was studied by the Health Sentinel Network of Castile and Leon (Spain) through a health examination and a structured questionnaire covering quality of life (EQ-5D-3), lifestyle habits, diet, working life and family health. A blood sample was taken for the study of biological and genetic markers. Chi Square and logistic regression OR with 95% confidence intervals were used to analyze the determinants of the long-lived individuals’ health status. The significant level for the bivariate analysis was established at 0.05. Results Perceived health was good, very good or excellent in 64.2%, while only 46.0% had a quality-of-life index above 0.5 (ranging from 0 to 1) and 44.1% maintained acceptable independence for activities of daily living. Quality-of-life index was higher in the oldest, (OR 7.98 [2,32-27.41]) above 100 years compared to those under 98, and men had better values for independence than women (OR 2.43 [1.40–4.29]). Cardiovascular diseases were the most prevalent (85.5%), but neurological and mental diseases and vision problems had the highest impact on quality of life and independence. Conclusion The long-lived individuals of Castile and Leon have a relatively well-preserved health status, although the perception of health is higher than that describing their quality of life and dependence. The quality of life was higher in the oldest age group and showed differences according to sex, with a better quality of life in men. Public health policies and programs should take in account the differences by sex and age as well as the prevention and control of the main conditions related with poor quality of life or dependence. Future research must include the interaction among genetic, socioeconomic, environmental, and other clinical factors in the quality of life and disability of long-lived individuals.